Reduced transport models for a tokamak flight simulator. (1st March 2023) - Muraca, M; Fable, E; Angioni, C; Luda, T; David, P; Zohm, H; Di Siena, A; Upgrade Team, the ASDEX
Abstract: In this work, a very fast integrated transport model involving every region that interacts directly with the plasma of a tokamak, has been developed. The confined region is modeled in 1.5D, while the scrape-off layer has a 0D structure. For the core region, a physics-based analytical regression based on a set of simulations with the transport model TGLF [Staebler 2005 Phys. Plasmas 12 102508] has been produced. For the H-mode regime, an average edge-localized-modes model is applied in the pedestal region. In the scrape-off layer a two-point model for electron temperature (exhaust) and a particle balance for the species density at the separatrix have been implemented. All the models have first been validated individually in a standalone setting. Finally, six fully integrated simulations of an L-mode discharge, and five H-mode discharges, have been performed in the Fenix flight simulator [Janky et al 2019 Fusion Eng. Des. 146 1926, Fable et al 2022 Plasma Phys. Control. Fusion 64 044002], including transients, matching the experimental trajectories of an ASDEX upgrade discharge during flat-top and ramp-down. A broader validation including more discharges and the ramp-up phase is planned for the near future.